2020
DOI: 10.1016/j.ymthe.2020.06.026
|View full text |Cite
|
Sign up to set email alerts
|

Adiponectin Stimulates Exosome Release to Enhance Mesenchymal Stem-Cell-Driven Therapy of Heart Failure in Mice

Abstract: Mesenchymal stem/stromal cells (MSCs) are cultured adult stem cells that originally reside in virtually all tissues, and the gain of MSCs by transplantation has become the leading form of cell therapy in various diseases. However, there is limited knowledge on the alteration of its efficacy by factors in recipients. Here, we report that the cardioprotective properties of intravenously injected MSCs in a mouse model of pressure-overload heart failure largely depend on circulating adiponectin, an adipocyte-secre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
84
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 110 publications
(87 citation statements)
references
References 61 publications
(117 reference statements)
3
84
0
Order By: Relevance
“…1A ). Western blots of each immunoprecipitate of human mesenchymal stem cell lysate, which expresses human T-cad ( 20 ), using the respective monoclonal antibodies are shown in Fig. 1B .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…1A ). Western blots of each immunoprecipitate of human mesenchymal stem cell lysate, which expresses human T-cad ( 20 ), using the respective monoclonal antibodies are shown in Fig. 1B .…”
Section: Resultsmentioning
confidence: 99%
“…Native APN stimulated exosome biogenesis and secretion by binding to T-cad ( 17 ). Recently, we found that mesenchymal stem/stromal cells (MSCs) expressed T-cad and produced many exosomes in response to APN ( 20 ). Heart protection by transplanted MSCs in a heart failure mouse model requires circulating APN and T-cad expression in MSCs to produce exosomes ( 20 ).…”
mentioning
confidence: 99%
“…Human AT-MSC-EVs transport different types of proteins [12,52,[57][58][59][60][61][62][63][64][65], RNAs [11,12,53,54,59,[64][65][66][67][68][69][70][71][72][73][74] and lipids [58]. Due to this variety of cargo molecules, AT-MSC-EVs are involved in a wide range of biological functions including migration, immune regulation, cell proliferation, angiogenesis, osteocyte metabolism and nerve regeneration (for a comprehensive review see ref.…”
Section: Cargo Of At-msc-evsmentioning
confidence: 99%
“…The biogenesis of EV is regulated by a variety of intracellular proteins, enzymes and signaling pathways including: (1) RNA-binding proteins such as hnRNPA2B1 and Argonaute-2; (2) membranous proteins such as Caveolin-1 and Neural Sphingomyelinases; (3) Rab GTPases, ARRDC1, and ESCRT complexes; (4) lipid rafts or membrane lipid microdomains; (5) cytosolic proteins (syntenin) and endosomal enzymes (Heparanase); and, 6) Intracellular calcium-signaling pathways [ 82 – 89 ]. Biogenesic processes can also be modulated by different extracellular stimuli including: (1) viral infection; (2) oncogenic transformation or stresses; (3) hypoxia; (4) alcohol exposure; (5) irradiation; (6) impaired autophagy; and, (7) circulating hormones, which all have important implications in elucidating the pathophysiological mechanisms for development of novel therapeutic targets [ 90 – 95 ].…”
Section: Extracellular Vesicles (Evs)mentioning
confidence: 99%